An Exploratory Research on Conflicts Faced by the Graduate Class Representatives from Kathmandu Valley - Chaudhary, Rajeshwor (Prajnik Bimarsha प्राज्ञिक विमर्श, 2025)
The study aims to identify conflicts or problems faced by the graduate class representatives from Kathamandu Valley . The study adopts a phenomenological approach . Thematic analysis was used to code the data and identify themes . This analysis includes an unstructured interview which was given by the CR to identify the problems faced by them in ten graduate colleges from the Kathmandu valley . Out of ten graduate colleges, 50 face-to-face, un-structured interviews were conducted with Class Representatives of 10 different graduate colleges from Kathmandu Valley . The CRs of each college are the respondent . Based on the individual interview given by the CRs, they face the problems related to the attendance which is used as internal marking of the students . Similarly, the problems related to the physical structure, programmes, jealousy, assignments and medical first-aid were also faced by the CRs in different gradual colleges .